2022
DOI: 10.3390/fishes7060310
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Artificial Diets for the Larviculture of Giant Kōkopu (Galaxias argenteus)

Abstract: The selection of artificial feed is critical to the success of larviculture of fin fish and requires knowledge of the varied species-specific dietary and nutritional requirements. With the emergence of commercial aquaculture of giant kōkopu, Galaxias argenteus, there is a need to understand the species-specific needs for artificial feeds in larviculture. Consequently, this study compares three commercial artificial dry feeds; Otohime, Artemac and O.range on the growth of recently weaned giant kōkopu. Larvae fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…However, these relative feed particle sizes are at the lower end of what is generally considered the optimum size range of 25%–60% of mouth gape width (Bremigan & Stein, 1994; Fernández‐Diaz et al, 1994; Østergaard et al, 2005; Shirota, 1970). Furthermore, giant kōkopu have been shown to achieve greater growth performance when fed live diets with much larger particle size to mouth gape ratios up to at least 70% (McKay & Jeffs, 2022b). Larval fish rely on visual and olfactory cues to locate and capture prey (Hubbs & Blaxter, 1986; Jones & Closs, 2016; Miller et al, 1988; Southgate & Partridge, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these relative feed particle sizes are at the lower end of what is generally considered the optimum size range of 25%–60% of mouth gape width (Bremigan & Stein, 1994; Fernández‐Diaz et al, 1994; Østergaard et al, 2005; Shirota, 1970). Furthermore, giant kōkopu have been shown to achieve greater growth performance when fed live diets with much larger particle size to mouth gape ratios up to at least 70% (McKay & Jeffs, 2022b). Larval fish rely on visual and olfactory cues to locate and capture prey (Hubbs & Blaxter, 1986; Jones & Closs, 2016; Miller et al, 1988; Southgate & Partridge, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is probable that the poor uptake of artificial feed at the earlier stages, that is, 18 and 21 DAH, is caused by the small size of the feed particles (i.e., 75–150 μm) and/or limited visual ability of the larvae to detect them, in contrast to the larger size of the Artemia nauplii (400–500 μm). Prior research has already shown Otohime to produce greater growth performance and survival over other formulated larval feeds of similar particle sizes (McKay & Jeffs, 2022a). However, from the present study, it would be advantageous to experiment with larger initial feed particle sizes with variable sinking rates to determine whether visual acuity at these very early stages of larval development are preventing earlier uptake of artificial feeds.…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, while the variety of ingredients that can be employed in artificial diets is virtually endless, the time and economic resources needed to test them are not. In their study, McKay and Jeff [5] compared three commercial diets for giant kokopu (Galaxias argenteus) larvae to identify the nutritional needs and improve their commercial aquaculture production. Indeed, they reported evident differences in groups fed different commercial diets.…”
mentioning
confidence: 99%